Genomic Organization, Phylogenetic and Expression Analysis of the B-BOX Gene Family in Tomato - Chu, Zhuannan; Wang, Xin; Li, Ying; Yu, Huiyang; Li, Jinhua; Lu, Yongen; Li, Hanxia; Ouyang, Bo (Frontiers in Plant Science, 2016)
The B-BOX (BBX) proteins encode a class of zinc-finger transcription factors possessing one or two B-BOX domains and in some cases an additional CCT (CO, CO-like, and TOC1) motif, which play important roles in regulating plant growth, development and stress response. Nevertheless, no systematic study of BBX genes has been undertaken in tomato (Solanum lycopersicum). Here we present the results of a genome-wide analysis of the 29 BBX genes in this important vegetable species. Their structures, conserved domains, phylogenetic relationships, subcellular localizations, and promoter cis-regulatory elements were analyzed; their tissue expression profiles and expression patterns under various hormones and stress treatments were also investigated in detail. Tomato BBX genes can be divided into five subfamilies, and thirteen of them were found to be segmentally duplicated. Real-time quantitative PCR analysis showed that most BBX genes exhibited different temporal and spatial expression patterns, such as SlBBX24, which was constitutively expressed with high abundance in nearly all tissues studied, and eight genes (SlBBX4, 5, 6, 11, 16, 18, 19, and 22) showed relatively higher expression levels in vegetative tissues and non-ripening fruits. The expression of most BBX genes can be induced by drought, polyethylene glycol-6000 or heat stress. Some BBX genes were induced strongly by phytohormones such as abscisic acid, gibberellic acid or ethephon. The majority of tomato BBX proteins was predicted to be located in nuclei, and the transient expression assay using Arabidopsis mesophyll protoplasts demonstrated that all the seven BBX members tested (SlBBX5, 7, 15, 17, 20, 22 and 24) were localized in nucleus. Our analysis of tomato BBX genes on the genome scale would provide valuable information for future functional characterization of specific genes in this family.